India's Withdrawal from RCEP: Understanding India's Independence Amid Trends in Global Economic Dependence - Pasek Acyuta Diwangkara Satyakusuma (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
The Indian government withdrew from the Regional Comprehensive Economic Partnership (RCEP), citing the need to protect domestic small businesses. However, critics from liberalist intellectuals argued that India's justification of economic nationalism seemed weak and should not be adopted. This study then adopts a structuralist perspective to understand India's withdrawal and challenges the liberal view that sees it as a missed opportunity. The research question is formulated: amid current criticism of liberal groups against the government's protectionist justification, how does structuralism explain India's withdrawal from RCEP to justify the withdrawal? This essay employs the Dependency Theory, which highlights how RCEP's structure places India in a peripheral position and creates a dependency that threatens India. This article aims to defend the withdrawal of the Indian government and demonstrate the relevance of structuralism which is believed to be increasingly outdated in the theoretical debate between structuralism and liberalism in the Global Political Economy. Keywords: Dependency Theory; Free Trade; India; RCEP; Structuralism Pemerintah India menarik diri dari Regional Comprehensive Economic Partnership (RCEP) dengan alasan perlunya melindungi usaha kecil dalam negeri. Namun, justifikasi tersebut menuai kritik dari akademisi liberal yang berpendapat bahwa nasionalisme ekonomi India tampak lemah dan tidak layak diadopsi berdasarkan teori liberal. Kajian ini kemudian mengadopsi perspektif strukturalis untuk memahami penarikan diri India dan menantang pandangan liberal yang melihatnya sebagai peluang yang terlewatkan. Pertanyaan penelitian dirumuskan sebagai berikut: di tengah kritik kelompok liberal saat ini terhadap justifikasi proteksionis pemerintah, bagaimana strukturalisme menjelaskan penarikan India dari RCEP Untuk membenarkan penarikan? Artikel ini menggunakan Teori Ketergantungan, yang menyoroti bagaimana struktur RCEP menempatkan India pada posisi periferi dan menciptakan ketergantungan yang mengancam India. Artikel ini bertujuan untuk membela penarikan pemerintah India dan menunjukkan relevansi strukturalisme yang diyakini semakin usang dalam perdebatan teoretis antara strukturalisme dan liberalisme dalam Ekonomi Politik Global. Kata kunci: India; Pasar Bebas; RCEP; Strukturalisme; Teori Dependensi